THE TUNISIAN CONSTITUTIONAL TRANSITION AND DEBATES: ISLAM, WOMEN AND OTHER ACTORS IN THE WAKE OF THE POST JASMINE REVOLUTION - Booley, Ashraf (Jurnal Syariah, 2020)
The Arab uprising in Tunisia, dubbed the Jasmine Revolution began in 2010, protesting against unemployment, corruption, injustice and the absence of basic freedoms. The Jasmine Revolution ousted Ben Ali, the then president who was in power for more than three decades in 2011. Post Jasmine Revolution saw Tunisia making commendable strides in its transition towards a new all-inclusive democratic political order. However, the transition process has not been without obstacles which could have had the effect of derailing the transition process, such as the assassination of activists Chokri Belaïd and Mohamed Brami, the role and place of Islam, the inclusion of women in the political transition and the most popular Islamic party Ennahda with its rumours of transforming Tunisia into an Islamic state were cause for great concern for all. However, despite these concerns, Tunisia’s new constitutional text is considered to be a radical departure from its previous constitutional texts. After the drafting of various drafts, the 2014 constitutional text has attained the status in the Middle Eastern And North African Region MENA Region as being the most liberal compared to other countries in the Mena Region. The 2014 constitutional provisions protect civil liberties, separates legislative, executive and judicial powers, guaranteeing women parity in political institutions, and declares that Islam is the country’s official religion while at the same time protecting religious freedom for all. An important facet is the homogeneity of Tunisian society – which although has some divisions, did not suffer fragmentation along religious, political, cultural or ethnic lines, as is the case in other Muslim states. This was accomplished by including all actors not only political parties, women’s groups and activists, religious activists, but also the various unions which represented the working class in Tunisia. The outcome was nothing short of being miraculous, bearing in mind the chaos that engulfed Tunisia during this period. One could argue that Tunisian listened to its people and advice of all, thereby minimising a terrible outcome.